PATIENT PERCEPTIONS AND EXPERIENCES OF ENDODONTIC TREATMENT IMPLICATIONS FOR ORAL HEALTH CARE - Nikšić, Adel; Jakupović, Vedran (Sanamed, 2026)
Background: Endodontic treatment is an essential procedure for preserving natural teeth and preventing further oral health complications. However, patients’ perceptions, knowledge, and anxiety related to root canal treatment may influence their willingness to undergo the procedure and their overall satisfaction with dental care. Aim: The aim of this study was to examine the association between demographic characteristics—such as gender, age, and educational level—and patients’ perceptions, attitudes, and expectations regarding endodontic treatment. Materials and Methods: A cross-sectional study was conducted using an anonymous online questionnaire among patients residing in Sarajevo Canton. A total of 171 participants who had previously undergone endodontic treatment completed the questionnaire. The questionnaire collected demographic data and information about patients’ knowledge of endodontic treatment, previous treatment experience, satisfaction with the information provided by the dentist, perceived pain or discomfort, communication with the dentist, and overall treatment experience. Data were analyzed using IBM SPSS Statistics version 22. Descriptive statistics were used to summarize the data, while the independent samples Student’s t-test and one-way analysis of variance (ANOVA) were applied to assess differences between groups. Statistical significance was set at p < 0.05. Results: The majority of participants were female (80.1%), and most had a university degree (60.8%). Male participants reported significantly higher satisfaction with the information provided, the dentist’s professionalism, and comfort during treatment compared to female participants (p < 0.05). Participants aged 41 years and older reported significantly higher satisfaction with communication, information provided, and overall treatment experience than younger age groups. Participants with a lower level of education reported significantly higher levels of pain or discomfort during or after treatment (p < 0.004). Conclusion: Patients generally showed a positive perception of endodontic treatment. Effective communication, adequate patient education, and the dentist’s professionalism play an important role in reducing anxiety and improving patient satisfaction and treatment experience.